Potensi dan Perbandingan Turbin Crossflow dengan Turbin Kaplan PLTMH Wisata Telaga - Muhammad Syafiudin; Resi Dwi Jayanti Kartika Sari; Rahman Arifuddin (Elposys: Jurnal Sistem Kelistrikan, 2025)
Microhydro power plants present a sustainable energy solution, especially for rural and remote areas like Telaga Jiwa in Sumber Porong Village, Malang. This study aims to evaluate the site's hydro energy potential and determine the most efficient turbine type between Kaplan and Crossflow for application in a small-scale MHP system. Field measurements of water discharge were conducted using the float-area method, while head elevation was obtained through Google Earth data combined with direct site verification. The analysis revealed an average discharge of 0.354 m³/s and an effective head of 9.35 meters, producing a theoretical power output of 24.13 kW. Based on performance analysis, the Kaplan turbine achieved an efficiency of 83%, slightly higher than the 80.5% efficiency of the Crossflow turbine, indicating Kaplan’s suitability for relatively stable flow and medium head conditions. The total system efficiency, accounting for turbine, generator, and transmission losses, reached 72%. This output is sufficient to provide electricity to approximately 86 households with an average daily consumption of 4.7 kWh. The study concludes that implementing an MHP at this location is technically feasible and can contribute significantly to rural electrification, reducing fossil fuel dependency, and supporting national energy resilience. The findings also offer a technical reference for future microhydro development in similar geographic and hydrological conditions.